Combatting Intimate Partner Violence Modelling Scalable Pathways for Sustainable Interventions in South Africa: The private sector as a critical ally to promote women's well-being, economic empowerment, and inclusion in the advancement of gender equity - Farhana Parker (Graduate School of Business (GSB), 2024)
Intimate partner violence (a subset of violence against women) is a large-scale and complex social, public health, and economic problem that has existed for many decades, primarily enabled by systemic gender inequality and rooted in patriarchal gender norms. This study focuses on the design and scalability of interventions that address intimate partner violence targeted at mothers. The emphasis on mothers was chosen given the high prevalence of intimate partner violence perpetrated by men against women across the social spectrum and the more significant impact and sustainability intervening at this level presents to advance social and economic progress in South Africa. The existing interventions and funding to address violence against women are predominantly directed to post-violence responses related to the effects of violence. Despite these efforts to tackle violence against women in South Africa, the challenge persists, and many gaps remain, exacerbated by the COVID-19 pandemic. The equal demand, importance, and effectiveness of pre-violence prevention interventions were evident in this study. However, the demand for and the dominance of the post-violence position underscores prevention as a critical priority. The study, therefore, revealed a limitation in the thought processes that inform the design, sustainability, and scalability, of prevention interventions which impedes the capability to bring about the large-scale systemic improvements and changes to combat violence against women in the medium to longer term. There has been minimal evidence of strategic, innovative, sustainable, long-term, and workable prevention pathways. This has made evident the significant need for alternative pathways and innovative business models to build additional designs and scalability pathways to address the problem. Therefore, the study endeavoured to identify alternative scalable pathways to prevent violence against mothers in Cape Town. In the context of this study, social and inclusive innovation principles and practices have been used to foreground this study to inform a new narrative to address the challenge more efficiently and effectively. Social innovation has been used as a lens to inform scalability and sustainability as well as inform the building of new innovative pathways and business models in the violence against women prevention ecosystem. The study adopted a qualitative research approach. Data was collected via semi-structured expert interviews and meetings on the topic area and analysed using content analysis. The study's findings revealed two fundamental priorities that include seven key practices. They are integral to influencing the design and scalability of interventions to catalyse large-scale change and bring about substantial systemic improvements in this ecosystem. These priorities encourage a new narrative to approach intimate partner violence and are indicative that violence against women can be changed if we approach it with a new intelligence. The fundamental priorities outlined in the findings include: (i) Reframing mental models to address violence against women. (ii) Developing scalable pathways and business models to influence systems change and combat violence against women. The two fundamental priorities outlined in the study's findings point to the need for a necessary social innovative legislative change in the private sector's role in supporting sustainable and scalable pathways to combat intimate partner violence and advance social and economic progress